THE PATH TO A SUSTAINABLE AND HAPPY FUTURE: EXAMINING THE INTERPLAY BETWEEN RENEWABLE ENERGY, GOOD GOVERNANCE, AND HAPPINESS INDEX IN G7 COUNTRIES (World Economics and Finance Bulletin, 2025)
The interconnection between sustainable development, social well-being, and human happiness is increasingly recognized today. This study represents a significant advancement in understanding this complex relationship by examining the factors influencing the happiness index in the Group of Seven (G7) developed countries, focusing on the role of renewable energy and effective governance. Utilizing a panel data approach (quantile panel regression) spanning from 2012 to 2023, the research investigated the impacts of various factors, including renewable energy consumption (REC), good governance index (GGI), income (GDP), inflation (INFL), and trade openness (TO). Holding other variables constant, an increase of one percent in REC, GGI, GDP, INFL, and TO is associated with happiness index increases ranging from 0.20 to 1.75 percent, 0.13 to 0.19 percent, 0.30 to 1.46 percent, a decrease of 0.05 to 0.09 percent, and an increase of 0.60 to 2.39 percent, respectively. The study's findings demonstrate that elevating renewable energy consumption, enhancing governance quality, fostering economic growth, and expanding trade relations significantly increase happiness levels in G7 countries. Conversely, an uptick in the inflation rate has a negative impact on the happiness index